Metaheuristic-based approach tooptimizing the weights in the TOPSISmethod for driver candidate performanceassessment - Sarić, Ivana; Vujadinović, Jasmina; Nikolić, Rale (Vojnotehnički glasnik / Military Technical Courier, 2025)
Abstract Introduction/purpose: Traffic safety and reliable driver selection are key components of modern transport systems. The aim of this paper is to improve the evaluation process of candidates performance in driving tests by applying multi-criteria decision-making and metaheuristic optimization. Based on the results obtained using the Vienna Test System, a TOPSIS-based model with adaptive weighting of evaluation criteria is proposed. Methods: The weights of the TOPSIS method were optimized using three metaheuristic algorithms: Genetic Algorithm (GA), Ant Colony Optimization (ACO), and Bee Colony Optimization (BCO). Two objective functions were used during optimization — AUC and F1-score — to examine their impact on model accuracy and stability. The experimental framework consisted of three parts: (1) comparison of GA, ACO, and BCO performance using AUC as the objective function, (2) analogous comparison using F1-score as the objective function, and (3) cross-comparison between AUC and F1-score optimized models. Results: The obtained results indicate that both the choice of metaheuristic algorithm and the objective function significantly influence the performance of the TOPSIS method. AUC-based optimization resulted in more stable models and better balance between successful and unsuccessful candidates, while F1-based optimization achieved higher sensitivity and better identification of successful candidates. Conclusions: Applying metaheuristic algorithms for weight optimization within the TOPSIS framework enables adaptive and more reliable candidate ranking, contributing to the development of intelligent driver selection systems and improved traffic safety. The results confirm that an appropriate choice of optimization algorithm and objective function can significantly enhance model accuracy and robustness.